Characteristics Of The Integration Of Islam, Science And Archipelago Culture Study - Nafidatul Fadilah; Moh. Roqib (Transformasi Manageria: Journal of Islamic Education Management, 2024)
Integration between Islam, science and Indonesian culture is an effort to unite and create a relationship between religious values, science and technology, and Indonesian culture. This aims to form an intellectual generation capable of upholding the values ​​of the Qur'an and Sunnah of the Prophet Muhammad SAW. in everyday life which cannot be separated from science and technology as well as the culture that exists in society. This research uses a case study method. To obtain data, researchers collected various kinds of scientific papers or data related to the characteristics of the integration of Islam, science and Indonesian culture. This research shows that Islam, science and Indonesian culture are related and can complement each other to cover each other's shortcomings. This means that in these three realms of knowledge there is a kind of common ground, especially in its tentative nature (uncertain or still subject to change). Even if taken further, namely from a religious perspective, all ontological object statuses, be it science, religion or culture, are one.